Estimating simple fiscal policy reaction functions for the euro area countries - Martin Plödt; Claire Reicher (Kiel Institute for the World Economy (IfW), 2014)
We formulate and estimate a simple fiscal policy reaction function for the euro area and individual euro area countries. Our reaction function allows for primary surpluses to feature three components: an anti-cyclical response of primary surpluses to the output gap, a response to the debt-GDP ratio, and an exogenous fiscal policy shifter. In line with the cyclical adjustment literature and in contrast with much of the previous time-series literature, we find a consistently strong anti-cyclical response of primary surpluses to the output gap for the euro area. We also find a consistently strong positive response of primary surpluses to the debt-GDP ratio. Our estimates are robust to different output gap measures and to different assumptions regarding the order of integration of observables. In addition, we provide statistical evidence in favor of our specification of a fiscal policy reaction function which features persistent fiscal policy shocks as opposed to an alternative specification found in the literature which features fiscal policy smoothing. Altogether, our results help to reconcile widely differing estimates from the literature, and we argue that our results may therefore provide guidance to forecasters and policymakers.
Keywords: E62; H61; H62; 330; fiscal reaction function; fiscal policy; fiscal rule; euro area; primary surplus